Reflection on the EU Directive on the Strengthening Certain Aspects of the Presumption of Innocence and of the Right to be Present at the Trial in Criminal Proceedings - Ilic Dimoski, Divna /Misoski, Boban (Faculty of Law Iustinianus Primus Skopje, 2021)
The authors of this paper reflect on the EU Directive 2016/343 on the strengthening of certain aspects of the presumption of innocence and of the right to be present at the trial in criminal proceedings and its impact on the Macedonian criminal procedure system. The presumption of innocence is settled by the ECtHR jurisprudence as one of the basic standards that lie in the heart of the fair trial concept. The article discusses the issue of public references to quilt and the obligation of the Member States to take the necessary measures to ensure that, for as long as a suspect or an accused person has not been proved guilty according to law, public statements made by public authorities, and judicial decisions, other than those on guilt, do not refer to that person as being guilty. Also, there is the question of the burden of proof for establishing the guilt of suspects and accused persons, and the requirement that it lies on the prosecution. At the same time, the right to remain silent and not to incriminate oneself, specifically closely related to the presumption of innocence, opens the question about the drawing of adverse inferences when the defendant remains silent or fails to answer a certain question. Notwithstanding the fact that the Court asserts these rights as fundamental, in a number
Keywords: EU directive, suspect, presumption of innocence, right to silence, right to be present at trial, criminal procedure